Influência do estresse hídrico e salino na germinação de urochloa decumbens e urochloa ruziziensis - Rocha Pereira, Maria Renata [UNESP]; Martins, Cibele Chalita; Ferreira de Souza, Guilherme Sasso [UNESP]; Martins, Dagoberto [UNESP] (Universidade Federal de Uberlândia (UFU), 2012)
Studies of the germination response of seeds subjected to artificial stresses are provided tools for better understanding of the survivability and adaptation of these species in natural stress conditions such as drought or saline soils, common in agricultural and forest regions, contributing significantly to the development of management strategies. Thus, the purpose of this study was to evaluate the possible effects of water and salt stress on germination of Urochloa decumbens and Urochloa ruziziensis. The test was conducted at the Faculty of Technology of São Paulo, campus of Capon Bonito. The seeds were sown with four replicates of 50 seeds in paper soaked in solutions with the potentials of 0.0, -0.2, -0.4 and -0.8 MPa, induced with polyethylene glycol (PEG 6000) and NaCl. The germination test was conducted at 25 degrees C in the presence of light, evaluating the first test score at seven days after sowing, and weekly germination (normal seedlings) until 35 days. We calculated the index of germination rate. The results allowed the conclusion that water stress causes a greater reduction in force, speed of germination and cumulative germination of seeds of U. decumbens and U. ruziziensis than salt stress. The species U. decumbens showed higher tolerance to water and salt stresses.

Os estudos relacionados com a resposta germinativa de sementes submetidas à condição de estresses artificiais são ferramentas para um melhor entendimento da capacidade de sobrevivência e adaptação destas espécies em condições de estresses naturais, como a seca e solos salinizados, comuns em regiões agrícolas e florestais, podendo contribuir significativamente para o desenvolvimento de estratégias de manejo. Assim, o objetivo deste estudo foi avaliar os efeitos dos estresses hídrico e salino na germinação de sementes de Urochloa decumbens e Urochloa ruziziensis. O ensaio foi conduzido na Faculdade de Tecnologia do Estado de São Paulo, campus de Capão Bonito. A semeadura foi realizada com quatro repetições de 50 sementes em papel umedecido com soluções nos potenciais osmóticos de 0,0; -0,2; -0,4 e -0,8 MPa, induzidos com polietileno glicol (PEG 6000) e NaCl. O teste de germinação foi conduzido a 25°C na presença de luz, avaliando-se a primeira contagem do teste aos sete dias após a semeadura e, semanalmente, a germinação (plântulas normais) até os 35 dias. Foi calculado o índice de velocidade de germinação. A análise dos resultados permitiu a conclusão de que o estresse hídrico acarreta maior redução no vigor, velocidade de germinação e germinação acumulada de sementes de U. decumbens e U. ruziziensis do que o estresse salino. A espécie U. decumbens apresentou maior tolerância aos estresses hídrico e salino.
Influence of saline and water stress on germination of Urochloa decumbens and Urochloa ruziziensis
Keywords: Osmotic potential; Osmotic stress; Force; Weeds; Salinity